PERMASALAHAN UPAH MINIMUM TENTANG HIDUP LAYAK, DAYA BELI, DAN DISPARITAS UPAH - Mujito, Mujito; Abadi, Slamet (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
Minimum Wage is the lowest monthly wage consisting of wages without allowances or basic wages and fixed allowances. The Central Government has established a wage policy as one of the efforts to realize the right of Workers/Laborers to a decent livelihood for humanity. Adjustments to the value of the Minimum Wage, both the Provincial and Regency/City Minimum Wage, are carried out every year using a calculation formula by considering and ensuring that purchasing power is not reduced. However, the comparison of the Provincial Minimum Wage and the Regency/City Minimum Wage creates a significant minimum wage disparity and creates unfair competition. Therefore, the author is interested in conducting research on "Minimum Wage Problems Regarding Decent Living, Purchasing Power, and Wage Disparity" with the aim of analyzing the problem of determining the minimum wage based on the provisions of the applicable Laws and Regulations on Minimum Wages and to solve the problem of the Minimum Wage regarding Decent Living, Purchasing Power, and Wage Disparity based on Law Number 6 of 2023 concerning Job Creation that has been amending several provisions in Law Number 13 of 2003 concerning Manpower and the Constitutional Court Decision Number 168/PUU-XXI/2023 in the case of Material Testing of Law Number 6 of 2023 concerning Job Creation. The research method used in this study is normative juridical. The results of the study show that the Determination of the Minimum Wage based on the Need for a Decent Life by taking into account productivity and economic growth in accordance with Law Number 13 of 2003 concerning Manpower, only determines the Components, Types, and Quality of Decent Living Needs, but does not establish the Specification of Decent Living Needs which causes differences in each region, does not provide instructions and explanations of productivity and economic growth, causes a minimum wage disparity. The Formula for Determining the Minimum Wage based on Inflation, Economic Growth, and Certain Indices in accordance with the Constitutional Court Decision Number 168/PUU-XXI/2023 in the case of Testing Law Number 6 of 2023 concerning Job Creation can solve the problem of the Minimum Wage regarding Decent Living, Purchasing Power, and Wage Disparity by considering the Variables of Inflation and Economic Growth in the formula for determining the Minimum Wage will ensure that the Purchasing Power of the minimum wage will not be decreased, the Certain Index is a variable of Decent Living Needs which includes food and beverages, clothing, housing, education, health, recreation, and old-age guarantees to realize Decent Living, and Standardization of Guidelines for Components, Types, Specifications, and Quality of Decent Living Needs to ensure that the calculation method of each region is the same that can solve the Wage Disparity.